Extranodal Non-Hodgkin Lymphoma of Sinonasal Cavities - Mulya Diprasta, Made Maylisca Theresia; Pratama, I Nyoman Satria; Wiranda, Gde Sukris (Green Publisher Indonesia, 2025)
Sinonasal non-Hodgkin lymphoma (NHL) is a rare extranodal malignancy, comprising only 0.2-2% of all NHL cases. The disease predominantly affects males in the fifth to seventh decades of life, with diffuse large B-cell lymphoma (DLBCL) being the most dominant subtype. Clinical manifestations are often non-specific, including unilateral nasal obstruction, epistaxis, and constitutional symptoms such as weight loss, posing challenges for early diagnosis. Definitive diagnosis requires tissue biopsy with histopathological and immunohistochemical examination, supported by radiological imaging to assess lesion extent. Primary management is medical with chemotherapy, often combined with radiotherapy, while surgical intervention is limited to diagnostic purposes. This case report demonstrates a rare case of bilateral sinonasal cavity NHL in a 55-year-old male patient.